THE EFFECT OF DARK SIDES OF LEADERSHIP ON MANAGERS’ PERFORMANCE AND ENGAGEMENT AS VARIABLE INTERVENING IN MANUFACTURING COMPANIES - Ita Mariza (Jurnal Instrumentasi dan Teknologi Informatika (JITI), 2020)
This study aims to identify leadership success factor to enhance productivity in manufacturing companies. Empirical research has been conducted on senior managers’ and employees’ perception of the impact of dark sides of leadership as a variable intervening factor on managers’ engagement and performance in Manufacturing Companies in Tangerang Indonesia. The dark side of leadership has manifested in one-way communication, uncompromising, harsh and coercive, limited tolerance behavior, in the hope for achieving target in the work place. The purpose of this paper is to investigate and explore the effect of negative and dysfunctional traits and behavior of leaders on managers’ engagement and performance. This thesis explores three theories and in manufacturing companies observational testing was carried out. Data has been obtained by surveys directly to the respondents (the plant head, senior managers and staff of manufacturing companies) (the plant head, senior managers and employees in manufacturing companies). 119 senior managers from 2 manufacturing firms in Tangerang, Indonesia, engaged in this study. The research approach consists of a field sample with easy sampling and the study of data from the Lisrel software, Structural Equation Modeling (SEM).The findings are as follows: a) dark side of leadership positively and significantly effect on employee engagement (H1); b) Engagement positively and significantly effect on employee performance (H2); c) dark side of leadership positively effect on employee performance directly but it is not significant. However, the limitations of this research are a) characterized by cross sectional and perceptual analyzes; b) the location all of the companies involved is in Tangerang. Indonesia. The managerial implication of this research, for certain conditions and situation, the dark traits and behavior of leaders are needed or can be accepted because have a positive effect in order to influence the behavior of employees and strengthen their engagement and improve the performance. In other words that to influence the behavior of employee (strengthen engagement, increase performance) a leader in manufacturing company can apply their methods to lead by combining charismatic, inspiring others, providing individualized support and serving as a role model combined with dark side of their leadership.The theoretical implications of this research is we provide evident to the concept developed by Manderscheid & Freeman (2012), that there is a paradox of leadership that not only the bright or positive side of leadership but also research on the dark side of leadership behaviors.